PENYELESAIAN SENGKETA PEMBATALANPERJANJIAN KONTRAK KERJA SEBELUM DANSESUDAH PANDEMI COVID 19 - Rossanti Qorry Aina, (Fakultas Hukum Universitas, 2021)
This study aims to examine the settlement of work contract disputes before and during the Covid 19 pandemic. An agreement is two parties who agree to each other accept achievements and give each other counter-achievements. The agreement has the same legal force as legislation. That is, the agreement is valid and legally binding on the parties. The Covid-19 pandemic has disrupted the continuity of agreements. The research method used is normative juridical. The results obtained in this study are that the settlement of agreement disputes carried out by most of the parties filed a lawsuit to the Court. With the aim of terminating the contract on a definite date and time or changing the contract by restoring its balance and the choice of method of dispute resolution is very dependent on the conditions and agreement of both parties. Keywords: Covid -19, Agreement Cancellation, Dispute Resolution